2022
DOI: 10.1177/09567976221104037
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory Threat Mitigates the Breakdown of Group Cooperation

Abstract: Humans are exposed to environmental and economic threats that can profoundly affect individual survival and group functioning. Although anecdotal evidence suggests that threat exposure can increase collective action, the effects of threat on decision-making have been mainly investigated at the individual level. Here we examine how threat exposure and concomitant physiological responses modulate cooperation in small groups. Individuals ( N = 105, ages 18–34 years) in groups of three were exposed to threat of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Per this perspective, as long as the defining features of a social dilemma are maintained and free-riding remains in the individual's best interest, neither the public good's efficiency nor its (in)equality in returns should matter (R. M. Dawes, 1980;van Dijk & De Dreu, 2021). This conjecture contrasts with empirical findings that cooperation is common and frequent, even when it comes at a potential cost to individual interests (Kerr & Kaufman-Gilliland, 1994;Lojowska et al, 2023;Ostrom, 1998;Rand & Nowak, 2013;van Dijk & De Dreu, 2021;Van Lange, 1999;van Vugt & Hardy, 2009;Weber & Murnighan, 2008). In addition, experiments have revealed that larger rather than smaller returns from public goods (i.e., efficiency) further boost such cooperation (e.g., Engelmann & Strobel, 2004;Gunnthorsdottir et al, 2007;Isaac & Walker, 1998;Lugovskyy et al, 2017;Rapoport, 1967;Reuben & Riedl, 2013;van den Berg et al, 2020;Vlaev & Chater, 2006;C.…”
Section: Efficiency and Equality Attractmentioning
confidence: 92%
“…Per this perspective, as long as the defining features of a social dilemma are maintained and free-riding remains in the individual's best interest, neither the public good's efficiency nor its (in)equality in returns should matter (R. M. Dawes, 1980;van Dijk & De Dreu, 2021). This conjecture contrasts with empirical findings that cooperation is common and frequent, even when it comes at a potential cost to individual interests (Kerr & Kaufman-Gilliland, 1994;Lojowska et al, 2023;Ostrom, 1998;Rand & Nowak, 2013;van Dijk & De Dreu, 2021;Van Lange, 1999;van Vugt & Hardy, 2009;Weber & Murnighan, 2008). In addition, experiments have revealed that larger rather than smaller returns from public goods (i.e., efficiency) further boost such cooperation (e.g., Engelmann & Strobel, 2004;Gunnthorsdottir et al, 2007;Isaac & Walker, 1998;Lugovskyy et al, 2017;Rapoport, 1967;Reuben & Riedl, 2013;van den Berg et al, 2020;Vlaev & Chater, 2006;C.…”
Section: Efficiency and Equality Attractmentioning
confidence: 92%
“…Axelrod, 2006a;Mateo & Johnston, 2000;Platek et al, 2004). Fitting these possibilities, altruistic helping and cooperation increase when people share a common fate (Lojowska et al, 2023), are physically proximate (Buchan et al, 2002;Handley & Mathew, 2020), or are more rather than less similar (Balliet et al, 2014;Bian & Baillargeon, 2022;Lane, 2016).…”
Section: From Individuals To Groups: Social Interdependence and Altru...mentioning
confidence: 99%
“…For example, people may (assume they) have more positive interdependence when they share a common fate ( Ayers et al, 2023 ; Tjosvold, 1998 ), are physically close rather than distant ( Carsten, 1995 ; Columbus et al, 2021 ), and are phenotypically similar rather than dissimilar ( Hammond & Axelrod, 2006a ; Mateo & Johnston, 2000 ; Platek et al, 2004 ). Fitting these possibilities, altruistic helping and cooperation increase when people share a common fate ( Lojowska et al, 2023 ), are physically proximate ( Buchan et al, 2002 ; Handley & Mathew, 2020 ), or are more rather than less similar ( Balliet et al, 2014 ; Bian & Baillargeon, 2022 ; Lane, 2016 ).…”
Section: The Formation and Evolution Of Groupsmentioning
confidence: 99%